“Epidemic” swimming pool dermatitis: a new disease. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 5-year-old boy was first observed due to bloody hand dermatitis. His mother reported not only that the child had nothing on the hands before entering the pool where he remained for 3 hours, but also that other 5 children, all aged between 3 and 5 years, had the same dermatitis, whereas older children did not have any problem. The physical examination (Fig. 1)showed an intense erythema of the fingertips of 2nd, 3rd and 4th fingers, more obvious on the right hand, where the 3rd finger had bled, than on the left one, more pronounced on the 3rd finger of both hands than on the second, severer on the second finger than on the fourth and nothing on the little finger and thumb. His mother confirmed that the child, not knowing how to swim, had long clung on to the edge of the pool, moving along it. The final diagnosis was dermatitis from rubbing on macerated skin.